prove using the Hilbert System
{not q} ⊢ (p→q)→(not p)

- anonymous

prove using the Hilbert System
{not q} ⊢ (p→q)→(not p)

- Stacey Warren - Expert brainly.com

Hey! We 've verified this expert answer for you, click below to unlock the details :)

- katieb

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

- anonymous

I'm supposed to use the 3 axioms of the Hilbert System and Modus Ponens to prove this

- anonymous

Using the Hilbert Axioms.
We state our given:
\[
\neg q \vdash (p\to q)\to\neg p
\]Using the fourth (or third primary axiom):
\[
(\neg p\to \neg q)\to(q \to p)
\]We contraposition the first clause, since they are equivalent statements, by the above logical axiom:
\[
\neg q \vdash (\neg q\to \neg p)\to\neg p
\]Since\[
\neg p\to \neg p
\]By a simple reduction, then:
\[
\neg q \to \neg p
\]QED.

- anonymous

I think I need to assume (not q) and use that with the Hilbert System to come to the conclusions that (p→q)→(not p)

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

- anonymous

sorry if the way I wrote that made it confusing

- anonymous

Oh, all right, sorry, that's not all too difficult, let me retype the above:

- anonymous

It's essentially the same proof, just that we assume only the first given to denote the second. We assume:
\[
\neg q, (p\to q)
\]To be true, along with the three logical actions in the Hilbert system.
We begin:
\[
(p\to q)\to (\neg q \to \neg p)
\]By (3):
\[
\left ( \lnot \phi \to \lnot \psi \right) \to \left( \psi \to \phi \right)
\]So:
\[
(\neg q \to \neg p)\to \neg p\wedge \neg q\to \neg p
\]Consequentially:
\[
\neg q \vdash (p\to q) \to \neg p
\]QED.

- anonymous

are you assuming p->q at the beginning?

- anonymous

Yes, you have to, otherwise nothing follows.

- anonymous

Because we would then have no relation between instance \(p\) and \(q\).

- anonymous

well the only assumption I think I can make is not q

- anonymous

and I can only use things I can derive from the 3 axioms or modus ponens

- anonymous

for example I could use axiom 1 to write ((~q) ->(p->(~q))

- anonymous

and use that like an assumption

- anonymous

at least this is my understanding of the hilbert proof system

- anonymous

This is my first time using it

- anonymous

Yeah, I only used axioms, the third axiom states the manipulation above, and there needs to be some relation for p, q, otherwise we can only imply \(q\to q\), or some other singly-defined tautology.

- anonymous

I don't understand how you went from (p→q)→(¬q→¬p) to the end

- anonymous

I can get to this point by manipulating the axioms

- anonymous

how can you get the end to be just (not p)

- anonymous

and I've never seen an ^ in any Hilber proofs before

- anonymous

You can take the first axiom (or a conjunction/disjunction operator, I don't know if you're allowed to use these, but that's what my proof contains):
An explicit-axiom proof would look like this, for
\[
(p\to q)\to (\neg q \to \neg p)
\]Thus, MP:
\[
\frac{\neg q\to\neg p,\neg q}{\therefore \neg p}
\]

- anonymous

I don't know what a conjunction/disjunction operator is.
the only thing I have available to me are these axioms
A1 (A -> (B->A))
A2 ((A -> (B->C)) -> ((A->B)->(A->C)))
A3 (((~A) -> (~B)) -> (B->A))
and modus ponens hich states
if we have A->B and A we can infer B

- anonymous

Well, yeah, I've already proven it using only those.

- anonymous

sorry for not responding, I had to catch a bus

- anonymous

hmm maybe I'm confused about how you wrote it then

- anonymous

It's all right... but I've already shown the proof with only those 3.. I can re-write it wholly, if you wish...

- anonymous

well can you explain how you use each axiom at each step?
From the examples I've been provided it seems like you need to start with an assumption like (~q) or one of the axioms with values substituted into it

- anonymous

I'm a little confused how you begin with (p→q)→(¬q→¬p)

- anonymous

actually that is axiom 3 isn't it with A=¬p and B=¬q

- anonymous

We assume:
\[\neg q, (p\to q)
\]To be true, along with the three logical actions in the Hilbert system.
We begin:
As given by Axiom (3) which states:
\[
\left ( \lnot \phi \to \lnot \psi \right) \to \left( \psi \to \phi \right)
\]Then:
\[
(p\to q)\to (\neg q \to \neg p)
\](Since, we can replace it the logical inverses of each operator)
So, by the above:
\[
\frac{\neg q\to\neg p,\neg q}{\therefore \neg p}
\]And we're done.

- anonymous

Yes, it is.

- anonymous

The Hilbert System allows one to replace any single instance \(\phi\) with whatever other instance we wish, so long as it holds true.

- anonymous

could you please explain where this part comes from? ¬q→¬p,¬q

- anonymous

We know by our previous deduction that:
\[
\neg q\to \neg p
\]Since we have:
\[
\neg q
\]Therefore:
\[
\neg p
\](Modus Ponens)

- anonymous

can you apply modus ponens to the end of a statement like that?

- anonymous

From what I've seen they only apply modus ponens to the whole thing

- anonymous

Well, the statement I gave IS Modus Ponens (MP). We're simply taking our final logical deduction given by our previous.

- anonymous

but we are only applying it to (¬q→¬p) rather than the whole (p→q)→(¬q→¬p)
can we assume (¬q→¬p) based on (p→q)→(¬q→¬p)?

- anonymous

or are you getting the assumption that (¬q→¬p) from somewhere else?

- anonymous

No, the assumption is reached by the previous statement. I think it's easier to write it out.
We have that (p implies q) implies (not q implies not p). Therefore, by our assumption, we can therefore say that, for anything that holds in (p implies q), such will also hold in (not q implies not p). With this, we give the statement that not p is true based upon the fact that not q is true as the statement previously given follows.

- anonymous

Treat \(p \to q\) as our premise, and \(\neg q \to \neg p\) as our conclusive statement.
Because we can say that, if \(\Gamma\vdash a\to b \), then, by MP:
\[
\frac{\Gamma\vdash a}{\Gamma \vdash b}
\]

- anonymous

so you are assuming (p→q) to infer that (¬q→¬p) then

- anonymous

Yep.

- anonymous

I don't think I can use (p→q) as an assumption though. I think the only thing I can use as an assumption is (¬q) unless I can derive (p→q) from one of the axioms

- anonymous

OK so I completely understand your solution now. But I need to write an explicit proof so I can't just convert (¬¬p→¬¬q)→(¬q→¬p) to (p→q)→(¬q→¬p). I need o show I can get the (¬¬p→¬¬q) with the axioms as well. Can you help me out with that please?

Looking for something else?

Not the answer you are looking for? Search for more explanations.